Dinámica de crecimiento, mortandad y supervivencia de la especie Cedrela Odorata L. "cedro" de la plantación N° 06 del CIEFOR- Puerto Almendra, Loreto - Perú. 2021 - Gallardo Gonzales, Rolando (2022)
The study was carried out in Forest Parcel No. 06 of 1 ha in Ciefor - Puerto Almendras, evaluating 200 Cedrela odorata plants, planted every 5 meters and in 10 strips. The greatest increase in diameter was presented by band 9 with a value of 0.35 mm between the first and last evaluation. Likewise, in height the greatest increase was presented by band 1 with a value of 28.81 cm between the first and last evaluation. The Chi-square test indicates that there is a significant difference between the averages of increase in diameter - height and the bands (p-value = 0.00 <? = 0.05. The survival of cedar plants varies between 70% to 100% survival, while mortality varied between 5 and 30%. The highest mortality was presented by band 9 with 6 dead plants, which represents 30% of the dead plants. The highest number of plants presented GOOD quality with 176 seedlings that represents 94.62% of the total, followed by REGULAR quality with 8 live individuals that indicates 4.32% and, finally, the least amount of individuals were observed in BAD quality with 2 seedlings that represented 1.08% of the total. At a general level in the experiment Excellent quality (band 1, 3, 5, 6, 9 and 10) was recorded for the Cedrela odorata seedlings at the end of the study. Similar studies are needed with other native forest species in Ciefor - Puerto Almendras.